Formação da autonomia leitora: reflexões a partir da estética da recepção - Laranjeiras, Sandra Zely Alves Silva (2019)
This study, linked to the research line Cultures, Formation and Pedagogical Practices of the Graduate Program of the Universidade Estadual de Feira de Santana - UEFS - Bahia, aims to understand the reading formation of High School students, starting from themselves, investigating how literary reading contributes to the formation of the autonomous reader in contemporary times, in the light of the Aesthetics of Reception (JAUSS, 1979). It is born of a set of inquiries emerged from my experiences as reader and professional that, intertwined, converge on two key questions: how to understand the process of formation of the reading autonomy of the students in public school, taking as a research basis the reception of the literary text? I emphasize the importance given to the idea that reading and writing practices are embedded in historical and social contexts, and therefore objects of study of the Social Sciences. To meet the demands of Society and Education, among the many dialogues established, I bring Theodor Adorno as a debater of these issues. Thus, reading workshops were held at the Landulfo Alves de Almeida State College, in Cruz das Almas, Bahia, with high school students, with the mediation of literary texts as interface with the constitution of autonomy. The aim of this research is to investigate the social and cultural contexts in which the experience of the reader is constituted. In this sense, the theoretical-methodological path for this research is based on the receptive relations of the reader-text, on the originality of this encounter and on the processes of negotiation and production of meanings for the literary text. In dialogue with the Aesthetics of Reception in Jauss (1979) and the Adornian theory (2000), I propose research as an event, because knowledge is a social construction that involves, in a dynamic process, the interlocution of concrete subjects for production of sense and meanings, which implies a way of being and being in the world, but also of understanding it. The data analyzed in this work, produced through an intervention project, enabled the dynamics of 10 literary workshops, were grouped in thematic blocks of analysis as a methodological choice that facilitates the understanding of the object of study. For the critical evaluation of the reading events that took place in the selected workshops, I referred to Bordini & Aguiar's (1993) Receptive Method as a starting point, since it is a method that allows the analysis of the data, giving us indicators from of readers' expectations. In this way, the theoretical contribution was systematized from the studies of Jauss (1979), for the Aesthetics of Reception, in permanent dialogue with Zilberman (1989) and Bordini & Aguiar (1993); de Silva (2013), Freire (1996) and Adorno (1995), for the reading autonomy; de Koch (2002) and Soares (1998) for the notion of reading as a contextualised practice of language use and reflection; by studying the use of workshops as research strategies by Spink & Medrado (2014) and by studies in literature and society such as Candido (2006). The analyzes carried out reveal that reading practices carried out with a focus on the critical reader, offer significant experiences in literature, which contributes to the creative activity of the young readers and to the sharing of sense and meanings among subjects. They also showed the relevance of the school's re-signification in offering practical emancipatory readings